Current Insights in Microbiome Shifts in Sjogren’s Syndrome and Possible Therapeutic Interventions - Tsigalou, Christina; Stavropoulou, Elisavet; Bezirtzoglou, Eugenia (Frontiers in Immunology, 2018)
Sjogren ’s syndrome (SS) is an autoimmune disease, amongst the most common ones, that targets mainly the exocrine glands as well as extra-glandular epithelial tissues.Their lymphocytic infiltration leads to manifestations from other organs (eg.kidneys,lungs,liver or thyroid), apart from sicca symptoms (xerostomia and keratoconjunctivitis).SS is more prevalent in women than in men (9:1) .Moreover, p.SS patients are in increased risk to develop lymphoma. Certain autoantibodies (eg.antibodies against ribonucleoprotein autoantigens Ro-SSA and La-SSB) are ultimate hallmarks for the disease.It was not known until recently that culture-independent techniques like Next Generation Sequencing (NGS) facilitate the study of the microbe communities in humans and scientists achieved to define the outlines of the microbiome contribution in health and disease. Researchers have started to investigate the alterations in diversity of the oral, ocular or intestinal microbiota in SS. Recent studies indicate that dysbiosis may play a significant role in SS pathogenesis. At the same time,the cause or effect is not clear yet because the dysfunction of salivary glands induces alterations in oral and intestinal microbiome which is linked to worsen of symptoms and disease severity. If the human microbiome proves to play a key role in pathogenesis and manifestation of SS, the next step could be new and promising therapeutic approaches such as probiotics or prebiotics. This mini review focuses on the alterations of microbiome of SS patients, their connection with immune tolerance and new therapeutic strategies involving diet manipulation towards future personalized medicine.